2005
DOI: 10.1016/j.molcel.2005.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Osmotin Is a Homolog of Mammalian Adiponectin and Controls Apoptosis in Yeast through a Homolog of Mammalian Adiponectin Receptor

Abstract: The antifungal activity of the PR-5 family of plant defense proteins has been suspected to involve specific plasma membrane component(s) of the fungal target. Osmotin is a tobacco PR-5 family protein that induces apoptosis in the yeast Saccharomyces cerevisiae. We show here that the protein encoded by ORE20/PHO36 (YOL002c), a seven transmembrane domain receptor-like polypeptide that regulates lipid and phosphate metabolism, is an osmotin-binding plasma membrane protein that is required for full sensitivity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 35 publications
2
58
0
1
Order By: Relevance
“…For example, osmotin is a tobacco PR-5 family protein and the homolog of adiponectin. This protein has a three-dimensionally overlapping domain with adiponectin, and activate AMP kinases via adiponectin receptors [16]. We also found that the extracellular domain of feline AD-R1 was almost identical to that of human AD-R1, suggesting that the AD-R1 agonists for human diabetes medication would also be effective for the cat.…”
Section: Discussionmentioning
confidence: 60%
“…For example, osmotin is a tobacco PR-5 family protein and the homolog of adiponectin. This protein has a three-dimensionally overlapping domain with adiponectin, and activate AMP kinases via adiponectin receptors [16]. We also found that the extracellular domain of feline AD-R1 was almost identical to that of human AD-R1, suggesting that the AD-R1 agonists for human diabetes medication would also be effective for the cat.…”
Section: Discussionmentioning
confidence: 60%
“…More importantly, suppression of AdipoRs expression by siRNA markedly reduced phosphorylation of AMPK induced by osmotin. These data suggested that osmotin seemed to activate AMPK through AdipoRs in mammalian C2C12 myocytes 27 (Figure 4).…”
Section: Development Of Novel Therapeutic Strategy Targeting Adiporsmentioning
confidence: 79%
“…22 Moreover, we showed that osmotin, which is present in fruits and vegetables, activated AMPK through AdipoRs in myocytes. 27 We are now screening for low molecular compounds, and for confirming the clinical effectiveness and usefulness of HMW measurement (Figure 4). …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Three therapeutic strategies targeting adiponectin and its receptors have been currently contemplated to tackle the metabolic and cardiovascular abnormalities commonly linked to obesity: (i) to increase adiponectin expression in white adipose tissue and plasma adiponectin levels using PPAR␥ agonists (54), (ii) to up-regulate AdipoR expression using PPAR␣ agonists (55), and (iii) to characterize novel AdipoR agonists to counteract obesity-associated reduced adiponectin sensitivity (56). In the present study, we have demonstrated that AdipoR1 and AdipoR2 interact to form homomers and heteromers that exhibit distinct adiponectin binding affinities and intracellular signaling properties.…”
Section: Discussionmentioning
confidence: 99%